Analisis Wacana Kritis Narasi Video Dan Komentar Terhadap Pengungsi Rohingya Di Youtube - Ramadhani, M. Fairuz; Anastasia, Viola; Belinda, Bela (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2024)
ABSTRACT This research aims to analyze the narratives contained in videos about Rohingya refugees and their comments on Youtube using Norman Fairclough's Critical Discourse Analysis (AWK) approach. This approach includes 3 dimensions of critical discourse analysis according to Fairclough. Namely: text, discursive practices, and social practices. From 3 videos about Rohingya refugees with a total of 9,677 comments, the results of the qualitative analysis show that Rohingya refugees are represented very negatively in the videos and comments through discriminatory stereotypes. The dominant narrative highlights them as “illegal immigrants”, a “social burden”, as well as a “lewd”, “dirty”, and even “dangerous” group because they are considered potential colonizers like “Israel”. This representation creates a polarization between “us” and “them”, creating and reinforcing discriminatory power relations. Through the analysis of the text dimension, it was found that frequent use of discriminatory terms such as “pervert”, “slob”, and “sneaky” builds a negative stigma against refugees. In the discursive practice dimension, the production and consumption of texts have reinforced social exclusion through narratives of nationalism and negative stereotypes. On the social practice dimension, the narratives in the videos and the comments show xenophobia and dehumanization, which contribute to the normalization of hate speech and aggressive attitudes towards refugees. The results of this study show that social media functions as an ideological reproduction tool that supports social exclusion of marginalized groups. In this context, negative representations of Rohingya refugees demonstrate the prioritization of nationalistic interests, rather than humanitarian responsibilities. This worsens the community's acceptance of the arrival and presence of Rohingya refugees. Keywords: Critical Discourse Analysis; Refugees; Representation of Rohingya; Social Media; Youtube ABSTRAK Penelitian ini bertujuan untuk menganalisis narasi yang terkandung dalam video mengenai pengungsi Rohingya beserta komentar-komentarnya di Youtube dengan menggunakan pendekatan Analisis Wacana Kritis (AWK) Norman Fairclough. Pendekatan ini mencakup 3 dimensi analisis wacana kritis menurut Fairclough. Yaitu: teks, praktik diskursif, dan praktik sosial. Dari 3 Video mengenai pengungsi Rohingya dengan jumlah 9.677 komentar, hasil analisis yang dilakukan secara kualitatif menunjukkan bahwa pengungsi Rohingya direpresentasikan dengan sangat negatif dalam video dan kolom komentar melalui stereotip yang diskriminatif. Narasi dominan menyoroti mereka sebagai sebagai “imigran gelap”, “beban sosial”, serta penjajah seperti “Israel”. Representasi ini menciptakan polarisasi antara “kita” dan “mereka”, menciptakan dan memperkuat relasi kuasa yang diskriminatif. Melalui analisis dimensi teks, ditemukan penggunaan istilah-istilah diskriminatif yang sering digunakan seperti “cabul”, “jorok”, dan “licik” yang membangun stigma negatif terhadap pengungsi. Pada dimensi praktik diskursif, produksi dan konsumsi teks telah mempertegas ekslusi sosial melalui narasi nasionalisme dan stereotip negatif. Pada dimensi praktik sosial, narasi pada video beserta komentar-komentarnya menunjukkan xenophobia dan dehumanisasi, yang berkontribusi terhadap normalisasi ujaran kebencian dan sikap agresif terhadap pengungsi. Hasil penelitian ini menunjukkan bahwa media sosial memiliki fungsi sebagai alat reproduksi ideologi yang mendukung ekslusi sosial terhadap kelompok marginal. Dalam konteks ini, representasi negatif Pengungsi Rohingya menunjukkan prioritas kepentingan nasionalisme, alih-alih tanggung jawab kemanusiaan. Hal ini memperburuk penerimaan masyarakat terhadap kedatangan dan keberadaan pengungsi Rohingya. Kata kunci: Analisis Wacana Kritis; Media Sosial; Pengungsi; Representasi Rohingya; Youtube